The genetic diversity and population structure of shallots (Allium cepa var. aggregatum) in Indonesia based on R gene-derived markers - LINA HERLINA; REFLINUR REFLINUR; SOBIR SOBIR; AWANG MAHARIJAYA; SURYO WIYONO (Society for Indonesian Biodiversity, 2019)
Abstract. Herlina L, Reflinur, Sobir, Maharijaya A, Wiyono S. 2019. The genetic diversity and population structure of shallots (Allium cepa var. aggregatum) in Indonesia based on R gene-derived markers. Biodiversitas 20: 696-703. Molecular markers are very useful for determining plant genetic diversity, especially when they are associated with useful traits. In shallots, type of markers still very limited. Therefore, development of new molecular markers is challenging if the future demand for this crop is to be met. The present study reports the genetic diversity analysis of 36 accessions of shallots using molecular markers derived from partial R gene sequences. Six polymorphic R gene-derived markers (Acepa-1, Acepa-2, Acepa-3, Acepa-4, Acepa-5, and Acepa-6) were developed and applied to analyze the genetic diversity of shallots in Indonesia. These loci produced a total of 963 alleles with an average of 0.51 + 0.77 alleles per marker. The polymorphic information content value ranged from 0.2784 to 0.5236 with an average of 0.36015. The markers were able to differentiate the shallot genotypes into three major clusters, suggesting that shallots are characterized by poor levels of genetic diversity in Indonesia. After further validation, the markers will be very useful, serving as tools to support the breeding of disease-resistant shallot varieties.